The Transformational Leadership of School Administrators and the Motivation of Teachers under Office of the Private Education Yala Province - Tayakareng, Masukree (Al-HIKMAH Journal, 2022)
The objectives of this research were 1) to study the level of The Transformational Leadership of School Administrators under Office of the Private Education Yala Province 2) to study the level of Motivation of Teachers under Office of the Private Education Yala Province 3) Comparison of the level of Transformational Leadership of School Administrators under Office of the Private Education Yala Province classified by gender and work experience. 4) Comparison of Motivation of Teachers under Office of the Private Education Yala Province classified by gender and school size 5) to study the relationship between Transformational Leadership of School Administrators and the Motivation of Teachers under Office of the Private Education Yala Province; School administration and teacher under Office of the Private Education Yala Province, Data analysis used frequency, percentage, average, standard deviation, T-Test, F-Test and Pearson’s Correlation Coefficient. The research results were as follows: 1) The overall level of Transformational Leadership of School Administrators under Office of the Private Education Yala Province was at a high level. 2) The overall level of Motivation of Teachers under Office of the Private Education Yala Province was at a high level. 3) Comparison of the level of Transformational Leadership of School Administrators under Office of the Private Education Yala Province classified by gender Overall is not different and Comparison of the level of Transformational Leadership of School Administrators under Office of the Private Education Yala Province classified by work experience was significantly different at the .05 level. 4) Comparison of Motivation of Teachers under Office of the Private Education Yala Province classified by gender and school size Overall is not different 5) The relationship between Transformational Leadership of School Administrators and the Motivation of Teachers under Office of the Private Education Yala Province; School administration and teacher under Office of the Private Education was positively correlated with teacher competency at the .01 level. The relationship was at a relatively high level. 6) Recommendations on Transformational Leadership of School Administrators and the Motivation of Teachers under Office of the Private Education Yala Province, namely, School administrators should have management or work that is a process or system, that is, school administrators should give praise, praise, welfare or gifts to teachers to create motivation and encouragement and security in life. There are special benefits according to the occasion. or every semester or every academic year School administrators should encourage teachers to come up with new methods or approaches to problem solving. And school administrators should assign tasks to teachers that are appropriate for their knowledge.